THE ASSOCIATION BETWEEN STROKE DETERMINANT FACTORS AND SLEEP QUALITY IN POST-STROKE PATIENTS - Afif, Zamroni; Arisetijono, Eko; Setijowati, Nanik; Sitompul, Boyke (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Background: Stroke is a serious condition can cause sudden loss of neurological function. Sleep disorders, such as insomnia, hypersomnia, sleep apnea, and restless leg syndrome, often occur in stroke patients and can worsen the post-stroke rehabilitation process, especially who have a history of diabetes mellitus (DM), hypertension, and heavy smoker. Effective management of post-stroke patients requires identifying and treating sleep quality disorders and associated risk factors to improve quality of life. Objective: This study aims to explore the association between DM, hypertension, and smoking in post-stroke patients and sleep quality. Methods: A cross-sectional study was conducted on post-stroke control patients at the Neurology Clinic at Dr. Saiful Anwar Hospital, East Java, from December 2023 to February 2024. Sleep quality disorder were measured using the Pittsburgh Sleep Quality Index (PSQI) within one month after outpatient treatment. Additional data were analyzed using the chi-square test and binary logistic regression. Results: Among the 74 participants, 25 patients (25.7%) had a history of DM, 68 (91.9%) with hypertension, and 20 (27%) were heavy smokers. There were 34 patients (45.9%) who experienced sleep quality disorders. There was a significant association between DM and sleep disorders (p=0.005), while hypertension and smoking did not show a significant correlation. History of DM was a significant predictor of sleep disorders (p=0.09 | OR 4.782, 95% CI 1.483–15.421). Conclusion: This study shows a significant association between history of DM in post-stroke patients and sleep quality based on PSQI.